Optimization of Gear Modification Amount based on Polynomial Response Surface Proxy Model - Yonghua Li; Wusong Wei; Xu Zhang (Jixie chuandong)
Aiming at the problem that gear modification is difficult to determine under the influence of multiple factors， the gear modification is optimized based on the polynomial response surface proxy model and particle swarm optimization algorithm. Firstly， considering the influence of the shaft and the bearing， the parametric modeling of the gear transmission device is carried out， and the transmission linear error， the maximum contact stress of the tooth surface and the unit normal load of the gear model are simulated and analyzed to determine gear modification mode for composite modification. Secondly， according to the model parameters and analysis results， the range of each shape modification parameter is determined， the orthogonal test design on the practice parameter is performed， and the test data is fitted to establish a polynomial response surface model. Finally， the particle swarm optimization algorithm is used to optimize the response surface model to obtain the optimal amount of gear modification. The results show that the fitted polynomial response surface proxy model has good accuracy and can accurately simulate the relationship between the gear modification parameters and the maximum contact stress. The optimal modification amount obtained by the particle swarm algorithm is used for gear modification， the maximum contact stress of the gear meshing process is reduced， the transmission error is reduced， and the eccentric load phenomenon is effectively improved.